2012
DOI: 10.1016/j.molcatb.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized redox enzymatic catalysts: Baeyer–Villiger monooxygenases supported on polyphosphazenes

Abstract: Abstract.A novel method has been employed for the selective covalent co-immobilization of a BaeyerVilliger monooxygenase (phenylacetone monooxygenase from Thermobifida fusca) and a NADPH recycling enzyme (glucose-6-phosphate dehydrogenase) on the same polyphosphazene carrier for the first time starting from {NP[O 2 C 12 H 8-x (NH 2 ) x ]} n , (x ranging from 0.5 to 2) using glutaraldehyde as connector. In all cases the preparation was active and it was found that the optimum proportion of amino groups in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…As shown in Table 1, covalent binding is the most common immobilization technique used for immobilization of isolated BVMOs. It is also true that utilization of isolated BVMOs resulted in loss of their enzyme activity despite immobilization (Mallin et al 2013;Cuetos et al 2012;Atia 2005). Moreover, it is not possible to compare results from different immobilization techniques due to inconsistency in choice of characterization parameters for immobilized isolated BVMOs listed in Table 1.…”
Section: Immobilization Of Isolated Bvmosmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, covalent binding is the most common immobilization technique used for immobilization of isolated BVMOs. It is also true that utilization of isolated BVMOs resulted in loss of their enzyme activity despite immobilization (Mallin et al 2013;Cuetos et al 2012;Atia 2005). Moreover, it is not possible to compare results from different immobilization techniques due to inconsistency in choice of characterization parameters for immobilized isolated BVMOs listed in Table 1.…”
Section: Immobilization Of Isolated Bvmosmentioning
confidence: 99%
“…On the other side, immobilized CHMO lost its activity during repeated biotransformation cycles. Decrease of relative activity of phenylacetone monooxygenase (PAMO) coimmobilized with G6PDH on polyphosphazene carrier during 5 cycles of benzyl acetate production was ascribed to low stability of PAMO (Cuetos et al 2012). A unique concept of polymersome nanoreactors was used for encapsulation of fusion protein CRE2-PAMO containing thermostable PAMO and NADPH regenerating phosphite dehydrogenase (Meeuwissen et al 2011).…”
Section: Immobilization Of Isolated Bvmosmentioning
confidence: 99%
“…Recently, it was shown that PAMO can also be covalently immobilized on polyphosphazenes yielding 8 U per gram of carrier after multiparametrical optimization [31]. However, in that case, a significant decrease of enzymatic performance was observed upon immobilization.…”
Section: Enzyme Immobilizationmentioning
confidence: 99%
“…PAMO has been coimmobilized with the NADPH recycling secondary enzymatic system (G6PDH) onto several polyphosphazene {NP[O 2 C 12 H 8−x (NH 2 ) x ]} n solid supports [39]. The biocatalysts were linked to the polymer through a glutaraldehyde connector.…”
Section: Sulfoxidations Catalyzed By Baeyer-villiger Monooxygenasesmentioning
confidence: 99%